Looking at Painting 2. - Adraken, M.; Dailey, Megan; Etchells, Tim; Gingeras, Alison, M.; Hager, Michael; Hoffert, Katrin; Majerus, Michel; Reinacher, Dane; Sanditz, Lisa; Wall, Jeff; s.n. (München : Galerie Tanit München, 2004)
van Eetvelde, Catharina ; Lang, Abigail ; Fabritius, Tom ; Hahn, Christian ; Hoffert, Katrin ; Van Imschoot, Jan ; Korty, David ; Magill, Elizabeth ; Majerus, Michel ; Morley, Ivan ; Nekarda, Kim ; Pérez, Enoc ; Sanditz, Lisa ; Waddell, Stephen
biog. per kunstenaar
Duits
Engels
Exhibition. Looking at Painting 2. Galerie Tanit München, 01.07.2004 - 04.09.2004.
boek